Liquid-gas and solid-gas separators - Duroudier, Jean-Paul (Industrial equipment for chemical engineering set., 2016)
Liquid-Gas and Solid-Gas Separators, part of the Industrial Equipment for Chemical Engineering set, details the magnetic properties of solids and their separation in a magnetic field. After a thorough description of the electronic filter and its functioning, numerical examples are given for the functioning of Venturi (which is a convergent-divergent). The centrifugal separator with superimposed plates theory is also developed alongside the screw-mud-pump. The author also provides the methods needed for understanding the equipment used in applied thermodynamics in the hope of encouraging students and engineers to self build the programs they need. Chapters are complemented with appendices that provide additional information and associated references.